Elucidating the gas phase thermochemistry and the H-atom abstraction reactions of triethyl phosphite - Zhu, Zhihan; Bruce, Frederick Nii Ofei; Gao, Yuke; Zhou, Chong Wen; Taufiq-Yap, Yun Hin; Qin, Fei; Cheng, Song; Curran, Henry; Li, Yang (American Chemical Society, 2026)
Triethyl phosphite (TEPI), an organophosphorus compound, offers potential applications in flame-retardant materials, organic synthesis, homogeneous catalysis, agrochemicals, and pharmaceutical intermediate production. However, TEPI has received little attention compared to more extensively studied phosphates and phosphonates, with its thermal decomposition and chemical reactivity, particularly under combustion and high-temperature conditions, remaining largely unexplored. This study addresses that gap by analyzing the thermochemical properties and reaction kinetics of TEPI to clarify its combustion behavior and support the accurate modeling of its reaction pathways. In this study, the M06-2X/6-311++G(d,p) level of theory was used for geometry optimization, vibrational frequency calculations, and dihedral scans. The single-point energies (SPEs) of TEPI and its five radicals were calculated at the MP2/cc-pVXZ (X = D, T, or Q) and CCSD(T)/cc-pVXZ (X = D, T) levels of theory. We applied complete basis set (CBS) extrapolation to these energies to improve the accuracy and approximate the basis set limit. The bond dissociation energies (BDEs) of TEPI were calculated using single-point energies (SPEs) corrected with zero-point energies (ZPEs), as well as total energies at zero Kelvin (TEZK) obtained from an average of composite methods, including G3B3, G2, CBS-QB3, and G3B3. The thermochemical properties of TEPI and the rate constants for hydrogen atom abstraction (HAA) reactions with molecular oxygen, O2, and various radicals: •H (hydrogen), •OH (hydroxyl), •CH3 (methyl), CH3O•̣̇ (methoxy), and HO2• (hydroperoxyl) were calculated using the Master Equation System Solver (MESS). The computed rate constants were further correlated with the corresponding energy barrier heights to elucidate their relationship. The results show that HAA from the secondary hydrogen site is more favorable than from the primary site, with the highest reaction rates observed for •H and •OH abstractions. With a kinetic mechanism still developing, additional reaction pathways such as hydrogen atom transfer and scission of various single bonds were estimated using rate constants derived by analogy. Furthermore, sensitivity analysis of the ignition delay time (IDT) confirmed the significance of HAA reactions, which control the initial consumption of TEPI. However, further refinement of the kinetic mechanism and experimental validation are necessary to fully confirm these reaction pathways and establish a robust model for TEPI’s behavior under practical conditions. These findings offer fundamental insights and quantitative kinetic parameters into TEPI’s reactivity, which serve as inputs for constructing detailed chemical kinetic models, thereby offering a quantitative basis for predicting its combustion behavior and optimizing its performance in flame-retardant applications.